Imaging concentration profile using laser based tomography - Mohd. Khafe, Adie (2007)
This project describes an investigation of the use of laser based tomography in the measurement of concentration profile of flowing particles. The main purpose is to investigate the use of an optical tomography method for on-line monitoring of particles. The novelty of this method is that it can be used to provide cross-sectional image of material distribution i.e. the concentration profile. This image is formed by reconstruction of data obtained from the array of sensors. Images of the flow captured using optical sensors are digitized into a form suitable for computer processing of the flow pictures. The advantages of this method is that it is cheaper and safer than most of the current methods which mostly made use of radioactive methods. Various process industries such as petroleum and food processing can benefit from such invention to improve their products and reduce the amount of wastage. Laser diode was used as the light source and photodiode are used as the receiving sensor in this project. The laser beam will be passed through the cross sectional area of the conveyer pipe and the emitted light will strike the photodiode located across the pipe. Besides the hardware, this project will include the use of user friendly, Visual Basic program to visualize the concentration profile of the flowing particles.